INTERNAL SOCIAL RESPONSIBILITY: A BUSINESS COMPETITIVENESS STRATEGY - Pereira, Zulay
The purpose of the article was to analyze internal social responsibility in companies, for which a descriptive methodology was used with bibliographic documentary review, applying hermeneutics in the findings. A prevalence of studies focused on the fulfillment of contractual legal commitments of the company with the collaborators, to achieve competitiveness was found. It is concluded that it is important for employers to focus more on managing internal social responsibility strategies aimed at the humanization of work environments.